1986
DOI: 10.1007/bf01296523
|View full text |Cite
|
Sign up to set email alerts
|

Urgency and fecal soiling in people with bowel dysfunction

Abstract: The frequency of urgency and fecal soiling in the population and among people with irritable bowel syndrome (IBS), and the association of these symptoms with health care seeking is unknown. Among 1128 students and hospital employees that we surveyed, urgency was reported in 14.4%, fecal soiling in 5.3%, and diarrhea in 9.0%. Most persons with fecal soiling did not report urgency or diarrhea. Although bowel dysfunction compatible with IBS was present in 20% (227), only 29% of this group (65) had seen a physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 8 publications
1
31
1
1
Order By: Relevance
“…The threshold of phasic sphincter contraction reverted to normal in the three patients with abnormal values. After retraining, squeeze duration increased significantly from 19-6 (2 4) to 38-3 (3-2) seconds (p<0-0001) with all patients gaining a squeeze duration of at least 20 seconds (Fig 2). At the first interview, 11 patients reported a substantial improvement in faecal continence (good responders according to our criteria).…”
Section: Biofeedback Treatmentmentioning
confidence: 99%
“…The threshold of phasic sphincter contraction reverted to normal in the three patients with abnormal values. After retraining, squeeze duration increased significantly from 19-6 (2 4) to 38-3 (3-2) seconds (p<0-0001) with all patients gaining a squeeze duration of at least 20 seconds (Fig 2). At the first interview, 11 patients reported a substantial improvement in faecal continence (good responders according to our criteria).…”
Section: Biofeedback Treatmentmentioning
confidence: 99%
“…People with mild fecal loss such as staining are unwilling to admit to themselves that they have an FI problem [9] . As the problem worsens and patients inevitably accept that they have FI, they are reluctant to disclose the problem to others [9][10][11][12][13][14][15] , with only 5%-27% seeking help from their doctors [15] . Lack of disclosure may be to the result of embarrassment, the erroneous belief that FI is a normal part of aging, or the perception that no treatment is available.…”
Section: Introductionmentioning
confidence: 99%
“…Although those seeing doctors appear over anxious, the apparent relationship between anxiety and symptoms may be an artefact of selective self referral as non-anxious individuals with similar symptoms may never consult a doctor. 3 The precise role of anxiety is thus uncertain and as only half of IBS patients are overtly anxious, it is clear that there must be other causes. Recent surveys have indicated that, depending on the country and whether they are in primary or secondary care, 6-17% of unselected IBS patients report that their IBS began with a bout of gastroenteritis.…”
mentioning
confidence: 99%